Short Communication An Interferon-gamma ELISPOT Assay with Two Cytotoxic T Cell Epitopes Derived from HTLV-1 Tax Region 161-233 Discriminates HTLV-1-Associated Myelopathy/Tropical Spastic Paraparesis Patients from Asymptomatic HTLV-1 Carriers in a Peruvian Population - Best, I (2011)
We thank the staff at the Instituto de Medicina Tropical Alexander von Humboldt for their valuable assistance in their attention to the HTLV-1-infected people. This work was supported by the Directorate-General for Development Cooperation of the Belgian Government through the Framework Agreement with the Institute of Tropical Medicine of Antwerp and through the Flemish Interuniversity Council (VLIR), and by the Peruvian National Board for Science and Technology (CONCYTEC).